Investigação sobre a realização do ensino remoto na Universidade Federal do Amazonas, durante o período de pandemia da COVID – 19 no município de Humaitá - Amazonas - Souza, Fábio Geraldo de (Brasil, 2023)
This text is the result of a research addressed within the scope of the Federal University of Amazonas, at the Institute of Education, Agriculture and Environment - IEAA/UFAM in the municipality of Humaitá, with the objective of investigating the realization of remote teaching at the Federal University of Amazonas, during the period of the COVID-19 pandemic in the municipality of Humaitá - Amazonas. The approach of this work consisted of two types of methods, being the quantitative and qualitative approach. To achieve the objectives, online questionnaires with objective and subjective questions were applied using the Google Forms platform, with IEAA/UFAM students. After approval of the project by the Research Ethics Committee under opinion number 5,185,547, participants received a Free and Informed Consent Term, explaining the objectives and methodologies of the project, after obtaining consent, the research links were made available via e-mails and WhatsApp in student groups. The survey was carried out with 60 IEAA students with the highest prevalence of the Biology and Chemistry course, representing 43% of the participants. The research showed little knowledge of the academic community about remote teaching before the beginning of classes, corresponding to 30% of the participants with no knowledge and 56%,7 with superficial knowledge about the teaching strategy, even being approved at UFAM months after its insertion of the strategy in the country. The remote period presented advantages and disadvantages, among the advantages, we highlight the continuity of classes even with a period of turmoil that the students were at the moment, time management, greater flexibility and autonomy of time, use of digital tools in teaching, the exemption of displacement and among others. The negative points highlighted by the students were: internet connectivity, accommodation, teacher-student interaction, student-student interaction, difficulties in understanding content and an appropriate place to study. This study shows a reality of remote teaching and it is clear that many points still need to be improved for a good use of teaching and learning, especially with connectivity as it is a study carried out entirely by internet. As an alternative to minimize the difficulties presented by academics, the Federal University of Amazonas, in future cases of application of remote teaching, should train the academic community on the teaching modality, before its application in the academic calendar. Another need is the availability of adequate physical space for carrying out studies, with good connectivity, for all academics who have difficulties with these aspects, during remote teaching.